2009
DOI: 10.1128/mcb.01590-08
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Histone Variant Exchange Accompanies Gene Induction in T Cells

Abstract: Changes in chromatin composition are often a prerequisite for gene induction. Nonallelic histone variants have recently emerged as key players in transcriptional control and chromatin modulation. While the changes in chromatin accessibility and histone posttranslational modification (PTM) distribution that accompany gene induction are well documented, the dynamics of histone variant exchange that parallel these events are still poorly defined. In this study, we have examined the changes in histone variant dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 56 publications
4
80
0
Order By: Relevance
“…Perhaps reminiscent of that model, induction of the CD69 and heparanase genes in T cells was correlated with the depletion of H2A.Z and concomitant deposition of H3.3 on the promoter. 46 Based on these results regarding promoters, it is tempting to speculate that H2A.Z eviction during transcription elongation may also be coupled to H3.3 deposition. Experiments in Drosophila revealed that nucleosomes were lost and replaced with H3.3-containing nucleosomes during activated transcription.…”
Section: Does H2az Mediate Its Various Functions Via Interactions Wimentioning
confidence: 98%
“…Perhaps reminiscent of that model, induction of the CD69 and heparanase genes in T cells was correlated with the depletion of H2A.Z and concomitant deposition of H3.3 on the promoter. 46 Based on these results regarding promoters, it is tempting to speculate that H2A.Z eviction during transcription elongation may also be coupled to H3.3 deposition. Experiments in Drosophila revealed that nucleosomes were lost and replaced with H3.3-containing nucleosomes during activated transcription.…”
Section: Does H2az Mediate Its Various Functions Via Interactions Wimentioning
confidence: 98%
“…It is generally thought that RNA polymerase and the transcriptional activation and elongation complexes destabilize nucleosomes, promoting nucleosome remodeling, and variant histone incorporation, which then further potentiate or stabilize gene expression (Bintu et al, 2011;Sutcliffe et al, 2009).…”
Section: Histone Variantsmentioning
confidence: 99%
“…Indeed, transcription induction coincides with H3.3 accumulation at several individual genes (20)(21)(22). However, recent reports based on detailed analysis of transcriptional and developmental phenotypes of flies that have been genetically manipulated to deplete H3.3 have challenged its functional significance in active transcription (23,24), because H3.3 was dispensable for most transcriptional events throughout Drosophila development.…”
mentioning
confidence: 99%